Drag Reduction Mechanism of Viscoelastic Slick-Water Fracturing Fluid in Tortuous and Rough Fractures - Zhiyu Liu; Fan Fan; Donghang Zhang; Yang Li; Yuan Li; Kai Yang; Hongkui Ge; Fujian Zhou (Geofluids)
Slick-water can effectively reduce the flow drag of fracturing fluid. Many studies have focused on the drag reduction performance of slick-water in wellbore and perforation, but there has been little research on drag reduction characteristics in fracture flow. In this paper, a new visualization experiment system is used to simulate real fracture. The fracture surface is produced through actual triaxial hydraulic fracturing and is copied by a three-dimensional printer using resin material to maintain its shape feature. In comparing the experimental results, it was found that the main factors affecting drag reduction in a fracture are the relative molecular weight and the added concentration. Unlike the flow rule of the drag reducer in a pipeline, when the concentration is greater than 0.10%, a negative DR effect begins to appear. The influence of molecular weight is related to the flow stage; the increasing of molecular weight causes a reduction in DR effect when the flow rate is 0.24 m/s. However, the flow rate exceeds 0.5 m/s; drag reducers with higher molecular weight demonstrate better drag reduction performance. The drag reduction mechanism analysis in fractures was obtained from visualization observations, and the flow characteristics of fluid were characterized by using tracking particles. Drag reduction effect occurs mainly on the surface of the fractures in contrast to near the centre of the flow channel. This research can provide a reference for the experimental study on drag reduction in fractures and is of great significance to the optimization and improvement of drag reducing agent.